Chondroprotection of PPARα activation by WY14643 via autophagy involving Akt and ERK in LPS‐treated mouse chondrocytes and osteoarthritis model. Issue 4 (7th February 2019) - Zhou, Yang; Chen, Xiaolei; Qu, Ning; Zhang, Bing; Xia, Chun
Abstract: Autophagy maintains cellular homoeostasis. The enhancement of autophagy in chondrocytes could prevent osteoarthritis (OA) progression in articular cartilage. Peroxisome proliferator‐activated receptor α (PPARα) activation may also protect articular chondrocytes against cartilage degradation in OA. However, whether the protective effect of activated PPARα is associated with autophagy induction in chondrocytes is not determined. In this study, we investigated the effect of PPARα activation by its agonist, WY14643, on the protein expression level of Aggrecan and ADAMTS5, and the protein expression level of autophagy biomarkers, including LC3B and P62, using Western blotting analysis in isolated mouse chondrocytes pre‐treated with lipopolysaccharides (LPS, mimicking OA chondrocytes) with or without the autophagy inhibitor chloroquine diphosphate salt. Furthermore, Akt and ERK phosphorylation was detected in LPS‐treated chondrocytes in response to WY14643. In addition, the effect of intra‐articularly injected WY14643 on articular cartilage in a mouse OA model established by the destabilization of the medial meniscus was assessed using the Osteoarthritis Research Society International (OARSI) histopathology assessment system, along with the detection of Aggrecan, ADAMTS5, LC3B and P62 protein levels using immunohistochemistry assay. The results indicated that PPARα activation by WY14643 promoted proteoglycan synthesis by autophagy enhancement in OA chondrocytes in vivo and in vitro concomitant with the elevation of Akt and ERK phosphorylation. Therefore, autophagy could contribute to the chondroprotection of PPARα activation by WY14643, with the implication that PPARα activation by WY14643 may be a potential approach for OA therapy.